Doing business in rural China : Liangshan's new ethnic entrepreneurs - Heberer, Thomas (Studies on ethnic groups in China., 2007)
"In Doing Business in Rural China, Thomas Heberer tells the stories of individual entrepreneurs and presents a wealth of economic data gleaned from extensive fieldwork in Liangshan. He documents and analyzes the phenomenal growth during the last two decades of Nuosu-run businesses, comparing these with Han-run businesses and asking how ethnicity affects the new market-oriented economic structure and how economics in turn affects Nuosu culture and society." "This book will appeal not only to China specialists, but also to those interested more broadly in ethnicity and the anthropology of economic development."--Jacket